Consumption of ultra-processed foods and non-communicable diseases-related nutrient profile in Portuguese adults and elderly (2015-2016): The Upper project - De Miranda, RC (2021)
This study aims to investigate the dietary share of ultra-processed foods and its association with non-communicable diseases (NCDs)-related nutrient profile of adult and elderly population in Portugal. Cross-sectional data from the National Food, Nutrition and Physical Activity Survey (2015-2016) of the Portuguese population has been analyzed. Dietary intake was assessed by two non-consecutive 24-h recalls and food items were classified according to the NOVA system. We estimated the percentage of dietary energy provided by each of the NOVA food groups and assessed the NCD-related nutrient profile of the overall diet across quintiles of ultra-processed foods consumption. Weighted t-Test, besides crude and adjusted linear and Poisson regressions have been performed. Ultra-processed foods contributed with around 24% and 16% of daily energy intake for adults and elderly, respectively. In both groups, as the consumption of ultra-processed foods increased, the dietary content of free sugars, total fats and saturated fats increased, while the dietary content of protein decreased. In adults, the total energy intake, the dietary energy density, and content of carbohydrates also increased as the consumption of ultra-processed foods increased, while the dietary content of fibre, sodium and potassium decreased. The prevalence of those exceeding the upper limits recommended for free sugars and saturated fats increased by 544% and 153% in adults, and 619% and 60% in elderly, when comparing the lowest to the highest quintile of ultra-processed consumption. Such a scenario demands for effective strategies addressing food processing in Portuguese population to improve their diet quality and prevention against diet-related NCDs. (c) The Authors 2020.